Emotional impact of COVID-19 on college students. A comparative study - Rodríguez de los Ríos, Luis Alberto (2020)
The objective of the research was to establish the differences in the emotional impact of COVID 19 among university students, according to their gender and educational management. The approach used was quantitative, non-experimental, descriptive and comparative design. The study population was 418 students of both sexes belonging to a public university and a private one. to whom the COVID-19 Emotional Impact Profile (PIE COVID-19) questionnaire prepared by García Pérez and Magaz (2020) was applied. The statistical analysis of the data obtained, allowed to establish differences at the level of sex in the emotional impact of COVID 19 in the dimensions: fear and depression, in favor of university students; And, according to educational management, there are no differences between university students in terms of the emotional impact of COVID 19.